Multiscale Observations of Deep Convection in the Northwestern Mediterranean Sea During Winter 2012–2013 Using Multiple Platforms. Issue 3 (5th March 2018) - Testor, Pierre; Bosse, Anthony; Houpert, Loïc; Margirier, Félix; Mortier, Laurent; Legoff, Hervé; Dausse, Denis; Labaste, Matthieu; Karstensen, Johannes; Hayes, Daniel; Olita, Antonio; Ribotti, Alberto; et al.
Abstract: During winter 2012–2013, open‐ocean deep convection which is a major driver for the thermohaline circulation and ventilation of the ocean, occurred in the Gulf of Lions (Northwestern Mediterranean Sea) and has been thoroughly documented thanks in particular to the deployment of several gliders, Argo profiling floats, several dedicated ship cruises, and a mooring array during a period of about a year. Thanks to these intense observational efforts, we show that deep convection reached the bottom in winter early in February 2013 in a area of maximum 28 ± 3 10 9 m 2 . We present new quantitative results with estimates of heat and salt content at the subbasin scale at different time scales (on the seasonal scale to a 10 days basis) through optimal interpolation techniques, and robust estimates of the deep water formation rate of 2.0 ± 0.2   Sv . We provide an overview of the spatiotemporal coverage that has been reached throughout the seasons this year and we highlight some results based on data analysis and numerical modeling that are presented in this special issue. They concern key circulation features for the deep convection and the subsequent bloom such as Submesoscale Coherent Vortices (SCVs), the plumes, and symmetric instability at the edge of the deep convection area. Key Points: We study deep convection and subsequent bloom in the northwestern Mediterranean Sea based on modern observation techniques We provide estimates of mass and energy fluxes over a period of a year in the deep convection area and deep water formation rates We highlight small‐scale circulation features that are important for deep convection and subsequent bloom and introduce this special issue